2016
DOI: 10.1136/gutjnl-2016-311739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GP2 IgA autoantibodies are associated with poor survival and cholangiocarcinoma in primary sclerosing cholangitis

Abstract: ObjectivePancreatic autoantibodies (PABs), comprising antibodies against glycoprotein 2 (anti-GP2), are typically associated with complicated phenotypes in Crohn's disease, but have also been observed with variable frequencies in patients with UC. In a previous study, we observed a high frequency of primary sclerosing cholangitis (PSC) in patients with anti-GP2-positive UC. We therefore aimed to characterise the role of anti-GP2 in PSC.DesignIn an evaluation phase, sera from 138 well-characterised Norwegian pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 35 publications
(42 reference statements)
7
48
1
1
Order By: Relevance
“…Jendrek et al [57] just recently demonstrated that anti-glycoprotein (GP)-2 immunoglobuline G autoantibodies are associated with the presence of CCA in patients with primary sclerosing cholangitis. In a large study comprising over 250 patients from Norway and Germany, it was shown that anti-GP2 positive PSC patients yield a significantly higher risk for CCA development than anti-GP2 negative patients.…”
Section: Resultsmentioning
confidence: 99%
“…Jendrek et al [57] just recently demonstrated that anti-glycoprotein (GP)-2 immunoglobuline G autoantibodies are associated with the presence of CCA in patients with primary sclerosing cholangitis. In a large study comprising over 250 patients from Norway and Germany, it was shown that anti-GP2 positive PSC patients yield a significantly higher risk for CCA development than anti-GP2 negative patients.…”
Section: Resultsmentioning
confidence: 99%
“…The second commonest autoantibodies are anti- Saccharomyces cerevisiae antibodies (ASCA), which also exhibit high frequency even in the absence of advanced disease or inflammatory bowel disease (IBD) [16]. Recently, Jendrek et al [17] also found an association between antibodies against glycoprotein 2 (anti-GP2) and large bile duct diseases with considerable rates. In PSC, anti-GP2 IgA was consistently identified in patients with poor survival during follow-up, being associated with cholangiocarcinoma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jendrek et al [17] also found an association between antibodies against glycoprotein 2 (anti-GP2) and large bile duct diseases with considerable rates. In PSC, anti-GP2 IgA was consistently identified in patients with poor survival during follow-up, being associated with cholangiocarcinoma [17]. Other autoantibodies including antinuclear antibody (ANA) and liver kidney microsomal type 1 antibody (anti-LKM1) can be positive in PSC patients, but with low specificity for the diagnosis of the disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such treatments are more selective against malignant cells and generally less toxic than traditional chemotherapy [82]. Conversely, antibodies against glycoprotein 2 are associated with more severe phenotype and poor survival due to cholangiocarcinoma [83].…”
Section: Immunotherapymentioning
confidence: 99%